Modern Operating Systems - Tanenbaum, Andrew S. 1944-; Bos, Herbert (Boston, [etc.] Pearson, 2015)
Operating Systems in Computer Science, Computer Engineering, and Electrical Engineering programs. The widely anticipated revision of this worldwide best-seller incorporates the latest developments in operating systems (OS) technologies. The Fourth Edition includes up-to-date materials on relevant OS. Tanenbaum also provides information on current research based on his experience as an operating systems researcher
Keywords: Sistemas operativos (Ordenadores)